Effects of plasma kallikrein deficiency on haemostasis and thrombosis in mice: Murine Ortholog of the Fletcher Trait - Bird, J. Eileen; Smith, Patricia L.; Wang, Xinkang; Schumacher, William A.; Barbera, Frank; Revelli, Jean-Pierre; Seiffert, Dietmar (Thrombosis and Haemostasis, 2012)
Plasma kallikrein is a multifunctional serine protease involved in contact activation of coagulation. Deficiency in humans is characterised by prolonged activated partial thromboplastin time (aPTT); however, the balance between thrombosis and haemostasis is not fully understood. A study of plasma kallikrein-deficient mice revealed increased aPTT, without prolonged bleeding time. Prekallikrein antisense oligonucleotide (ASO) treatment in mice suggested potential for a positive therapeutic index. The current goal was to further define the role of plasma kallikrein in coagulation. Blood pressure and heart rate were normal in plasma kallikrein-deficient mice, and mice were completely protected from occlusion (100 ± 1.3% control flow) in 3.5% FeCl3 -induced arterial thrombosis versus heterozygotes (20 ± 11.4%) and wild-type littermates (8 ± 0%). Vessels occluded in 8/8 wild-type, 7/8 heterozygotes, and 0/8 knockouts. Anti-thrombotic protection was less pronounced in 5% FeCl3-induced arterial injury. Integrated blood flow was 8 ± 0% control in wild-type and heterozygotes, and significantly (p<0.01) improved to 43 ± 14.2% in knockouts. The number of vessels occluded was similar in all genotypes. Thrombus weight was significantly reduced in knockouts (−47%) and heterozygotes (−23%) versus wild-type in oxidative venous thrombosis. Average tail bleeding time increased modestly in knockout mice compared to wild-type. Average renal bleeding times were similar in all genotypes. These studies confirm and extend studies with prekallikrein ASO, and demonstrate that plasma kallikrein deletion prevents occlusive thrombus formation in mice with a minimal role in provoked bleeding. Additional support for the significance of the intrinsic pathway in the coagulation cascade is provided, as well as for a potential new anti-thrombotic approach.
Keywords: Protease; animal model; gene knockout